Beyond Financial Incentives: Exploring the Lived Experience of EV Adopters in an Urban Context - Sapkota, Roman; Acharya, Khagendra (Apex Journal of Business and Management, 2025)
Electric vehicles (EVs) are promoted in many countries as a sustainable option to internal combustion vehicles (ICEVs). In Nepal, where such promotion is done through measures such as supportive tax, the uptake of private electric passenger vehicles (PEPVs) is a major concern. This study examines the motivations and challenges related to EVs adoption in a capital city of Nepal, Kathmandu, with the aim of capturing how consumer perceptions and experience shape adoption dynamics. A descriptive phenomenological design was adopted for the study. Five participants, comprising both adopters and potential adopters, were selected through purposive sampling, and structured interviews were conducted. The participants’ responses were transcribed and analyzed using Giorgi’s phenomenological method. Findings highlight financial pragmatism as the dominant driver of adoption, particularly long-term savings on fuel and maintenance. However, these incentives are offset by persistent anxieties about high battery replacement costs, uncertain resale value, and long-term depreciation. Infrastructural gaps, such as unreliable charging networks, reinforce emotional strain and consequently discourage broader use. Policy volatility and weak communication of incentives undermine consumer confidence, while safety perceptions remain ambivalent, balancing recognition of advanced features with concern about malfunctions and fire risks. The study concludes that financial incentives alone are insufficient; sustainable EV adoption requires stable policies, reliable infrastructure, and proactive public engagement to build consumer trust and confidence.